Persepsi Pembelajaran Daring - Winatun Navis (Universitas Muhammadiyah Gresik, 2023)
The research was conducted with the aim of knowing more deeply about student perceptions of online learning systems. The method used by the author is a quantitative descriptive research method with a purposive sampling technique using 34 students as subjects. Collecting data using a questionnaire. The results showed that most students preferred the offline learning method. Online learning is quite easy for the current learning system, but in some cases there are still some obstacles such as ineffective learning due to poor internet connection so that students do not fully get the gist of lectures that day.